The Appliance of Science? The Theory and Practice of Crime Intelligence Analysis - Innes, Martin (The British journal of criminology, 2005)
Intelligence analysis has emerged as an important component of contemporary policing strategies. Drawing upon qualitative data and a perspective informed by some of the concepts associated with the sociology of scientific knowledge, this paper provides an epistemologically oriented critique of some of the key techniques associated with crime analysis. Data presented suggest that crime analysis: is used in line with traditional modes of policing; is a way of claiming scientific objectivity' for police actions; and is largely shaped by police perspectives on data. It is argued that the sense of enhanced objectivity often attributed to the products of intelligence work' is frequently overstated. The products of crime analysis are better understood as an artefact of the data and methods used in their construction, rather than providing an accurate representation of any crime problems